Cancer chemopreventive activity of xanthohumol, a natural product derived from hop - Gerhäuser, Clarissa; Frank, Norbert; Bartsch, Helmut (Molecular cancer therapeutics, 2002)
Characterization and use of effective cancer chemopreventive agents have become important issues in public health-related research. Aiming to identify novel potential chemopreventive agents, we have established an interrelated series of bioassay systems targeting molecular mechanisms relevant for the prevention of tumor development. We report anticarcinogenic properties of Xanthohumol (XN), a prenylated chalcone from hop (Humulus lupulus L.) with an exceptional broad spectrum of inhibitory mechanisms at the initiation, promotion, and progression stage of carcinogenesis. Consistent with anti-initiating potential, XN potently modulates the activity of enzymes involved in carcinogen metabolism and detoxification. Moreover, XN is able to scavenge reactive oxygen species, including hydroxyl- and peroxyl radicals, and to inhibit superoxide anion radical and nitric oxide production. As potential antitumor-promoting mechanisms, it demonstrates anti-inflammatory properties by inhibition of cyclooxygenase-1 and cyclooxygenase-2 activity and is antiestrogenic without possessing intrinsic estrogenic potential. Antiproliferative mechanisms of XN to prevent carcinogenesis in the progression phase include inhibition of DNA synthesis and induction of cell cycle arrest in S phase, apoptosis, and cell differentiation. Importantly, XN at nanomolar concentrations prevents carcinogen-induced preneoplastic lesions in mouse mammary gland organ culture. Because XN is easily cyclized to the flavanone isoxanthohumol, activities of both compounds were compared throughout the study. Together, our data provide evidence for the potential application of XN as a novel, readily available chemopreventive agent, and clinical investigations are warranted once efficacy and safety in animal models have been established.